Exploring the antifungal and anti-virulence potential of alizarin against candida dubliniensis using an in vivo candidiasis model and shotgun proteomic approaches - Arumugam, Ganeshkumar (Universidade Estadual Paulista (Unesp), 2024)
Candida dubliniensis is one of the most common yet relatively unexplored fungal species present in the oral cavity of healthy individuals, with elevated levels often observed in HIV/AIDS patients. Although various studies have highlighted the importance of the Candida genus in pathogenesis and clinical manifestations, research specifically addressing drug discovery and development on C. dubliniensis remains limited. In this context, the present study aimed to investigate the potential of alizarin, a naturally occurring anthraquinone found in various plants, to inhibit the growth and primary virulence factors of C. dubliniensis. Preliminary investigations demonstrated that alizarin exhibited notable antifungal activity against both clinical and ATCC strains, with a minimum inhibitory concentration (MIC) of 16 µg/mL and a minimum fungicidal concentration MFC) 2048 µg/mL. Similarly, alizarin improved the antifungal activity of fluconazole by showing synergetic effect. To further validate its antifungal potential, a Galleria mellonella candidiasis model was employed. Remarkably, larvae treated with the MIC concentration of alizarin showed a significant reduction in fungal burden, along with improved survival rates as revealed by Kaplan-Meier analysis using the Mantel-Cox test (p = 0.028 for the ATCC strain and p = 0.0035 for the P3 4 clinical isolate). The immunomodulatory effects of alizarin were also assessed by analyzing G. mellonella haemocytes via flow cytometry. Comparative analysis of haemocyte populations indicated distinct immune responses between treatments with amphotericin B and alizarin. Although alizarin enhanced immune responses against fungal infection, its efficacy was lower compared to the standard antifungal treatment. Moreover, alizarin was found to inhibit major virulence behaviors at 16 µg/mL even after two hours of exposure. After 24 hours, only 2.12% of the cells retained the ability to transition into hyphal forms (p < 0.0001). Proteomic analysis revealed that alizarin significantly modulated the protein expression profile of C. dubliniensis, particularly downregulating proteins involved in cell wall synthesis and integrity maintenance. Overall, the present findings confirm that the phytochemical alizarin exerts antifungal effects against C. dubliniensis primarily by inhibiting its morphological transition. Further research is warranted to elucidate the detailed molecular and physiological mechanisms underlying alizarin’s antifungal action.
Exploring the antifungal and anti-virulence potential of alizarin against candida dubliniensis using an in vivo candidiasis model and shotgun proteomic approaches
Keywords: Candida dubliniensis; Infecções fúngicas invasivas; Alizarina; Candida dubliniensis; Invasive fungal infections; Alizarin